If f ( x ) = x + x 1 and g ( x ) = x − x 1 , f ( g ( 3 ) ) = b a , where a and b are positive, coprime integers. What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice
could someone break this down for me, I tried following along with the work that is provided but I am confused with a couple of things. I get the math provided for g(x) but for f(x) I get 10/3 and I was under the impression that 24 is not considered a co prime number.
Log in to reply
I think you got the definition of co-prime wrong. Co-prime is always between two or more numbers. So, when you say 24 is not a co-prime number, you should ask with respect to which number. Here, when you substitute 3 for x in g(x), you get the value 8/3. Now, when you substitute 8/3 for x in f(x), you get the value 73/24. Here, 73 and 24 are considered co-prime numbers because they do not have a common divisor (except for 1). That is what co-prime means. Two numbers a and b are co-prime when they do not have any common divisor other than 1. So here, 73/24 is considered to be a/b. When you add them, you get the result 97. I hope this made it clear.
f(x) = 73/24 so 73+24=97
I think your issue is that you calculated f ( 3 ) = 3 + 3 1 = 3 1 0 . While this is true, it is not what the question asked for.
We have f ( g ( 3 ) ) = f ( 3 8 ) = 2 4 7 3 .
Log in to reply
@calvin You forgot to mention what equation asked for is 3- 1/3 for g(3) while virginia mistook it as 3+1/3 which is just for f(3) not for g(3)
i understand it
OMG...this is so annoying.............my friends who are nice in math with me ,,,didn't get it.how's that??
g(3) = 3 - 1/3 = 8/3 f(g(3)) = 8/3 - 1/8/3 = 8/3 - 3/8 = 73/24 = a/b a= 73, b = 24 a+b = 97
Isn't f(x) = x + 1/x, why you use minus instead of plus? Just curious :)
first, find the solution of g(x), g(x)= g(3)=x-1/x = 3-1/3 = (9-1)/3 = 8/3 ................(1) Now, putting value of g(x) on fucntion f(x) i.e. putting 8/3 for finding f(g(3)) = x + 1/x = 8/3 +3/8 = (64+9)/24 = 73/24. therefor, f(g(3)) = 73/24 ................(2) As given in problem f(g(x)) =a/b .................(3) comparing equation (2) & (3) a/b = 73/24 therefore, a+b = 73+24 = 97. answear
keep it up
g(3)=3-1/3=8/3 f(g(3))=8/3-3/8=73/24 a=73 b=24 a+b=73+24=97
14, never learn +math
g(3) = 8/3 f(g((3))= 73/24 73+24=97
well done
f(g(x))=(x-(1/x))+1/(x-(1/x)) if x=3 then f(g(3))=73/24 a=73&b=24,as they are coprime integers. Hence,a+b=73+24=97
good
g ( x ) = x − x 1
g ( 3 ) = 3 − 3 1
which gives 3 8
f ( x ) = x + x 1
f ( g ( 3 ) ) = 3 8 + 8 3
which simplifies to 2 4 7 3
But b a + 2 4 7 3
Therefore a + b = 7 3 + 2 4
9 7
sorry b a = 2 4 7 3
g(3)=8/3
f(8/3)=73/24
73+24=97
g ( 3 ) = 3 − 3 1 = 3 8 . f ( g ( 3 ) ) = f ( 3 8 ) = 3 8 + 8 3 = 2 4 7 3 . Answer is a + b = 7 3 + 2 4 = 9 7
Solution - First of all, evaluate g(3) . To do this, all we have to do is to put the value 3 in the function: g ( x ) = x − x 1 g ( 3 ) = ( 3 ) − ( 3 ) ( 1 ) g ( 3 ) = 3 ( ( 3 × 3 ) − 1 ) g ( 3 ) = 3 ( 9 − 1 ) g ( 3 ) = 3 8
Now, the value of g(3) serves as argument for the function f(x) , and hence we evaluate the value of f(g(3) : f ( g ( 3 ) ) = 3 8 + 3 8 1 f ( g ( 3 ) ) = 3 8 + 8 3 f ( g ( 3 ) ) = 3 × 8 ( 8 × 8 ) + ( 3 × 3 ) f ( g ( 3 ) ) = 2 4 6 4 + 9 f ( g ( 3 ) ) = 2 4 7 3
Now, since 73 and 24 are co-primes , & hence satisfy the given condition for variables a and b . We have, a= 73; b=24 . Finally, calculating a+b , we get: a + b = 7 3 + 2 4 = 9 7 So, required solution is 97 .
Problem Loading...
Note Loading...
Set Loading...
g(x)=3-1/3=8/3 f(x)=8/3+1/8/3=73/24 73+24=97